Radiometry of water-containing myocardial tissue in patients with arterial hypertension - I. V. Terekhov; K. A. Solodukhin; V. S. Nikiforov; A. V. Lomonosov (Российский кардиологический журнал, 2013)
Aim. To study the water-containing myocardial tissue in patients with arterial hypertension (AH), using the ultra-high frequency (UHF) radiometry method, in order to assess myocardial function parameters. Material and methods. In total, echocardiography was performed in 30 patients, aged 40–60 years, with Stage I–III AH and Functional Class I–III chronic heart failure. Myocardial radiometry was performed with the diagnostic complex “Aquatone”, which assesses the status of water-containing tissues using the resonance probe radio emission (1 GHz) and stimulated tissue emission (65 GHz). Results. There was a strong negative correlation between the radio signal intensity and left ventricular posterior wall thickness (r=–0,96), myocardial mass index (r=–0,82), and end-systolic dimension (r=–0,66), as well as a strong positive correlation with end-diastolic dimension (r=0,55) and ejection fraction (r=0,73). Conclusion. The results obtained suggest the presence of pronounced changes in myocardial radio-physical characteristics in AH patients, as manifested in the disturbed myocardial ability to transform the external probe emission into the stimulated one.